Meniscal Tear at Knee: Repair or Resect? An Early Experience from a University Hospital in Nepal (Kathmandu University Medical Journal, 2022)
Background The meniscus plays an important role in maintaining healthy articular cartilage. Meniscus tear, one of the common intra-articular knee lesions, is treated by either debridement or repair.Objective This study aims at identifying the early outcome of meniscus tears treated by debridement or repair. This study also elaborates on the spectrum of meniscal injuries presented in a tertiary care hospital in Nepal.Method A retrospective descriptive cross-sectional study was conducted at Orthopedic Department of Dhulikhel Hospital from February 2018 until January 2020 among patients who underwent knee arthroscopies for meniscal tears treated either by debridement or repair. Patients having intra articular fractures, osteochondral injuries and multi-ligament injuries were excluded. The meniscal tears were classified according to location and type of tear. Those patients who had at least one-year of follow up were evaluated with Lysholm score for functional outcome. Data were compiled and analyzed with Microsoft Excel 2011.Result One hundred and ten cases of meniscal tears were managed over the study period. Ninety-three cases could be traced for outcome evaluation, which included 50 cases of meniscal debridement and 43 cases of meniscal repair. The mean Lysholm score of the patients who received debridement was 81.5 (SD 10.4) and those who received meniscal repair was 84.9 (SD 9.1) (p=0.105). The population distribution was found to be similar in both the groups according to age and sex distribution and associated ligamentous injuries.Conclusion Good functional outcome was seen for meniscal tears managed with debridement or repair in at least one year follow up and could not establish one modality of management better than the other.